2012
DOI: 10.1371/journal.pone.0041228
|View full text |Cite|
|
Sign up to set email alerts
|

A Replication Study Confirms the Association of Dendritic Cell Immunoreceptor (DCIR) Polymorphisms with ACPA - Negative RA in a Large Asian Cohort

Abstract: ObjectivesDendritic cell immunoreceptor (DCIR) has been implicated in development of autoimmune disorders in rodent and DCIR polymorphisms were associated with anti-citrullinated proteins antibodies (ACPA)-negative rheumatoid arthritis (RA) in Swedish Caucasians. This study was undertaken to further investigate whether DCIR polymorphisms are also risk factors for the development of RA in four Asian populations originated from China and Malaysia.MethodsWe genotyped two DCIR SNPs rs2377422 and rs10840759 in Han … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…Therefore, the finding that DCIR plays a major role in limiting CHIKV-induced inflammatory disease represents the first demonstration that a CLR plays a major role in the pathogenesis of alphavirus-induced arthritis. This result is consistent with prior studies which have shown that DCIR polymorphisms are associated with susceptibility to rheumatoid arthritis in humans (46,66,67) and modulate the severity of collagen-induced arthritis in mice (44,62). It is interesting that these studies showed that increased DCIR expression correlates with rheumatoid arthritis occurrence and severity.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the finding that DCIR plays a major role in limiting CHIKV-induced inflammatory disease represents the first demonstration that a CLR plays a major role in the pathogenesis of alphavirus-induced arthritis. This result is consistent with prior studies which have shown that DCIR polymorphisms are associated with susceptibility to rheumatoid arthritis in humans (46,66,67) and modulate the severity of collagen-induced arthritis in mice (44,62). It is interesting that these studies showed that increased DCIR expression correlates with rheumatoid arthritis occurrence and severity.…”
Section: Discussionsupporting
confidence: 92%
“…Because DCIR polymorphisms were associated with several noninfectious inflammatory disorders in humans (17)(18)(19), we asked whether DCIR could play a part in modulating immunity in the context of a chronic inflammation of infectious nature, namely TB. We first found that DCIR is expressed at the periphery of lung granulomas in M. tuberculosis-infected nonhuman primates (NHPs), a model that closely mimics TB in humans, during both asymptomatic infection and active TB disease (SI Appendix, Fig.…”
Section: Dcir Expressionmentioning
confidence: 99%
“…The novel associations at PRL and NFIA add to the list of suggestive or confirmed anti‐CCP–negative RA susceptibility loci: PTPN22, TNFAIP3, C5orf30, STAT4, BLK 8, SPP1 16, CLEC16A 17, IRF5 18, DCIR 19, 20, CLYBL 14, SMIM21 14, and ANKRD55 21. However, only a few of those associations have been independently replicated or confirmed at genome‐wide levels of significance.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously tested markers of anti‐CCP–positive RA for their association with anti‐CCP–negative RA 8 and reported that several anti‐CCP–positive RA susceptibility loci (e.g., AFF3, CCR6, CCL21, IL2RA, and CD28 ) were not shared with anti‐CCP–negative RA, while markers at TNFAIP3, C5orf30, STAT4, ANKRD55, BLK, and PTPN22 were associated with both anti‐CCP–positive and anti‐CCP–negative RA. In addition, CLYBL 14, SMIM21 14, SPP1 16, CLEC16A 17, IRF5 18, and DCIR 19, 20 have been reported to be associated with anti‐CCP–negative RA. Of the markers reported to be associated with anti‐CCP–negative RA, only CLYBL 14, SMIM21 14, and ANKRD55 21 have been independently replicated or confirmed at genome‐wide levels of significance.…”
mentioning
confidence: 99%